2014
DOI: 10.1016/j.nlm.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

From Pavlov to PTSD: The extinction of conditioned fear in rodents, humans, and anxiety disorders

Abstract: Nearly 100 years ago, Ivan Pavlov demonstrated that dogs could learn to use a neutral cue to predict a biologically relevant event: after repeated predictive pairings, Pavlov's dogs were conditioned to anticipate food at the sound of a bell, which caused them to salivate. Like sustenance, danger is biologically relevant, and neutral cues can take on great salience when they predict a threat to survival. In anxiety disorders such as posttraumatic stress disorder (PTSD), this type of conditioned fear fails to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
287
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(308 citation statements)
references
References 234 publications
(325 reference statements)
4
287
0
8
Order By: Relevance
“…The core deficit in PTSD has been conceptualized as pathological fear conditioning with a failure to recall extinction (Pitman, 1988; VanElzakker, Dahlgren, Davis, Dubois, & Shin, 2014). Animal models and human studies of PTSD have highlighted aberrations in neural circuitry including hyperactivity in the amygdala and dorsal anterior cingulate cortex, regions that promote fear responses, alongside hypoactivity in the ventromedial prefrontal cortex (vmPFC), a region that is thought to suppress fear responses (Milad & Quirk, 2012; Quirk, Garcia, & González‐Lima, 2006; VanElzakker et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core deficit in PTSD has been conceptualized as pathological fear conditioning with a failure to recall extinction (Pitman, 1988; VanElzakker, Dahlgren, Davis, Dubois, & Shin, 2014). Animal models and human studies of PTSD have highlighted aberrations in neural circuitry including hyperactivity in the amygdala and dorsal anterior cingulate cortex, regions that promote fear responses, alongside hypoactivity in the ventromedial prefrontal cortex (vmPFC), a region that is thought to suppress fear responses (Milad & Quirk, 2012; Quirk, Garcia, & González‐Lima, 2006; VanElzakker et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The core deficit in PTSD has been conceptualized as pathological fear conditioning with a failure to recall extinction (Pitman, 1988; VanElzakker, Dahlgren, Davis, Dubois, & Shin, 2014). Animal models and human studies of PTSD have highlighted aberrations in neural circuitry including hyperactivity in the amygdala and dorsal anterior cingulate cortex, regions that promote fear responses, alongside hypoactivity in the ventromedial prefrontal cortex (vmPFC), a region that is thought to suppress fear responses (Milad & Quirk, 2012; Quirk, Garcia, & González‐Lima, 2006; VanElzakker et al., 2014). More specifically, vmPFC engagement during extinction learning predicts extinction success and is associated with “top‐down” modulation of amygdala‐driven fear expression (Do‐Monte, Manzano‐Nieves, Quiñones‐Laracuente, Ramos‐Medina, & Quirk, 2015; Lebrón, Milad, & Quirk, 2004; Milad et al., 2005, 2007; Phelps, Delgado, Nearing, & LeDoux, 2004; Quirk, Likhtik, Pelletier, & Paré, 2003; Rosenkranz, Moore, & Grace, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of translational research has identified the interaction of several neurobiological mechanisms underlying the mammalian response to traumatic stress (for recent review, see (VanElzakker et al, 2014). For example, in rodents, activation of the hypothalamicpituitary-adrenal (HPA) axis invokes stress-induced plasticity in limbic structures such as the amygdala (Roozendaal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is often seen as a laboratory model of phobia or posttraumatic stress disorder (VanElzakker, Dahlgren, Davis, Dubois, & Shin, 2014). This is why ongoing research programs seek to elucidate the neural microcircuits supporting this type of learning (Bach, Weiskopf, & Dolan, 2011; Ciocchi et al, 2010) and possibilities to prevent (Grillon, Cordova, Morgan, Charney, & Davis, 2004; Reist, Duffy, Fujimoto, & Cahill, 2001), or even erase (Kroes et al, 2014; Schiller et al, 2010) fear memory.…”
mentioning
confidence: 99%